Diseño de un sistema automatizado de riego y dosificación de fertilizantes y nutrientes para cultivo hidropónico de la Empresa Vegetales Hidropónicos y Orgánicos LTDA (2022)
In the last decade, hydroponic crops in Colombia have increased close to 200%. However, there are major drawbacks to the implementation of this type of crop, such as high investment costs, complex infrastructure and difficulties in obtaining initial capital. In addition to this, the vast majority have manual irrigation and chemical dosing systems, thus incurring high operating costs and possible human errors that substitute crop nutrition. In order to increase the productivity and efficiency of the crop, it is necessary to implement new technological tools, such as microcontrollers, software and sensors, which can increase the precision of irrigation and mixing of the necessary nutrients, through the continuous control of variables such as they are pH, temperature, humidity, electrical conductivity and flow; approached from the perspective of automation in Mechanical Engineering using key concepts that allow the realization of an optimal and flexible design that adapts to the needs of the crops. Regarding the results obtained, it is perfected to correctly characterize the production process, with which the appropriate components are selected to carry out the measurement and control of variables. The programming code works correctly and is modified to perform a validation of it in a prototype which works properly.